The role of the 5′-3′ exoribonuclease XRNA in transcriptome-wide mRNA degradation - Manful Gwira, Theresa; Fadda, Abeer; Clayton, Christine (RNA, 2011)
The steady-state level of each mRNA in a cell is a balance between synthesis and degradation. Here, we use high-throughput RNA sequencing (RNASeq) to determine the relationship between mRNA degradation and mRNA abundance on a transcriptome-wide scale. The model organism used was the bloodstream form of Trypanosoma brucei, a protist that lacks regulation of RNA polymerase II initiation. The mRNA half-lives varied over two orders of magnitude, with a median half-life of 13 min for total (rRNA-depleted) mRNA. Data for poly(A)+ RNA yielded shorter half-lives than for total RNA, indicating that removal of the poly(A) tail was usually the first step in degradation. Depletion of the major 5′-3′ exoribonuclease, XRNA, resulted in the stabilization of most mRNAs with half-lives under 30 min. Thus, on a transcriptome-wide scale, degradation of most mRNAs is initiated by deadenylation. Trypanosome mRNA levels are strongly influenced by gene copy number and mRNA half-life: Very abundant mRNAs that are required throughout the life-cycle may be encoded by multicopy genes and have intermediate-to-long half-lives; those encoding ribosomal proteins, with one to two gene copies, are exceptionally stable. Developmentally regulated transcripts with a lower abundance in the bloodstream forms than the procyclic forms had half-lives around the median, whereas those with a higher abundance in the bloodstream forms than the procyclic forms, such as those encoding glycolytic enzymes, had longer half-lives.